Analysis of Development Needs for Android-Based Lower Passing Tests - Syariah Syariah; Destriana Destriana; Destriani Destriani (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to find out about the needs analysis for the development of an android-based lower passing test at senior high school N 1 Tanjung Batu. This research method uses a quantitative descriptive method. This research uses accidental sampling technique. The samples obtained were 539 students and 1 physical education teacher. The instruments in this study used a questionnaire to test the validity and reliability as well as closed interviews. Data analysis in this study used descriptive statistical percentages in the form of frequency tables. Based on the results of the study, it was found that 60% of students in class X (ten) really needed it, students in class XI (eleven) with a result of 59% who chose it really needed it and in class XII the results obtained were 71% who chose it really need it, meaning that class XII needed more development Android-based lower passing test compared to 2 (two) other classes. It was generally stated that 63% of Tanjung Batu 1 Public High School students and physical education teacher interviews were in the category of really needing the development of an android-based lower passing test. As a recommendation that this development in the future can continue to be carried out to support progress and ease in carrying out the lower passing test in volleyball games.